2005
DOI: 10.1111/j.1365-2842.2005.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometric assessment of treatment effects of maxillary protraction combined with chin cup appliance on the maxillofacial complex

Abstract: The aim of this study was to investigate the treatment effects on the maxillofacial complex by maxillary protraction combined with chin cup therapy among growing children. An effective geometric morphometric assessment of cephalometric radiographs, using Procrustes analysis and thin-plate spline analysis, was applied to evaluate shape change in the craniofacial and midfacial configurations of a treated sample of 20 children with skeletal Class III malocclusion. This was compared with matched untreated skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
1
18
1
1
Order By: Relevance
“…14 Similar findings were reported in earlier studies. 2,4 In contrast to the earlier reports, 3,17 our study showed significant reduction of Co-Go. The study showed positive OJ in all patients at end of CC therapy.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…14 Similar findings were reported in earlier studies. 2,4 In contrast to the earlier reports, 3,17 our study showed significant reduction of Co-Go. The study showed positive OJ in all patients at end of CC therapy.…”
Section: Discussioncontrasting
confidence: 56%
“…Chin cup is the preferred appliance for growing children with mandibular prognathism. [1][2][3] Chin cup is designed to suppress and/or redirect the mandibular growth, close the gonial angle, and remodel the mandibular and temporomandibular joint. The CC appliances can be divided into two subcategories: The vertical pull CC and the occipital pull CC.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability coefficients were from 0AE973 to 1AE00, indicating a high level of reliability. These had been previously assessed (11,24,25).…”
Section: Samplementioning
confidence: 99%
“…Mandibular prognathism or skeletal Class III malocclusion with a prognathic mandible has long been viewed as one of the most severe maxillofacial deformities (7). Facial growth modification can be an effective method of resolving skeletal Class III jaw discrepancies with dentofacial orthopaedic appliances (10, 11). Nevertheless, continued growth in early adulthood may detract from treatment results obtained in childhood or adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations evaluated skeletal changes produced by either rapid maxillary expansion and face mask therapy 44 or maxillary protraction in association with a chincup 45 . Where the maxillary expansion and protraction study showed less pronounced maxillary changes when compared with the effects of the treatment protocol used in this study.…”
Section: Discussionmentioning
confidence: 99%